2021
DOI: 10.3390/medicina57030286
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Reality and Treatment for Local Recurrence of Rectal Cancer: A Single-Center Retrospective Study

Abstract: Background and Objectives: Despite advances in treatment, local recurrence remains a great concern in patients with rectal cancer. The aim of this study was to investigate the incidence and risk factors of local recurrence of rectal cancer in our single center over a 7-year-period. Materials and Methods: Patients with stage I-III rectal cancer were treated with curative intent. The necessity for radiotherapy and chemotherapy was determined before surgery and/or postoperative histopathological results. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…In the present study, it was the therapeutic choice in 35.5% of patients. 26 This study shows data similar to those of the literature in most respects, such as incidence of local recurrence and the site of distant recurrence. However, some results serve as a stimulus for the search for improvement in surgical and drug treatment to increase patients' disease-free survival.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, it was the therapeutic choice in 35.5% of patients. 26 This study shows data similar to those of the literature in most respects, such as incidence of local recurrence and the site of distant recurrence. However, some results serve as a stimulus for the search for improvement in surgical and drug treatment to increase patients' disease-free survival.…”
Section: Discussionsupporting
confidence: 88%
“…The average age of the study patients was slightly higher than 63 years and was typical for colorectal cancer patients [31]. The importance of reduced activity, especially within the elderly patients, was also highlighted by Ekblom-Bak et al, whose study of the compliance with physical activity recommendations within an elderly population showed that minimum physical activity requirements were met by as few as 7% of subjects [32].…”
Section: Discussionmentioning
confidence: 87%
“…Observations were carried out over a period of one year after surgery and should be treated as early results of the surgical treatment. Notably, the recurrence of colorectal cancer is most frequently observed within the first 2–3 years after surgical treatment, with early recurrences being uncommon [ 36 ]. On the other hand, pain, including low back pain, may be associated with local recurrence or spread of the disease [ 37 ].…”
Section: Discussionmentioning
confidence: 99%